SISTEM PENGELOLAAN LAYANAN SERVIS SMARTPHONE BERBASIS WEB PADA PHONE REPAIR - M.Addien Gilang (Universitas Lampung, 2026)
Abstract. This research aims to design and develop a web-based smartphone service management system at PHONE REPAIR to assist administrative processes previously conducted manually using paper notes. Problems identified include the risk of data loss, difficulties in searching service data, report recapitulation, and lack of transparency regarding repair status information for customers. The system development method used is the Software Development Life Cycle (SDLC) with the Waterfall model consisting of requirement analysis, system design, coding, testing, and maintenance stages. System design was carried out using Unified Modeling Language (UML), including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The system was developed using the Laravel framework with Model View Controller (MVC) architecture, PHP programming language, MySQL database, and Visual Studio Code as code editor. System testing was conducted using Black box Testing and White box Testing methods to ensure functions and program logic run according to requirements. Research results indicate that the developed system assists administrators in managing service data, updating repair statuses, managing invoices, and generating reports in a more structured manner compared to manual processes. In addition, customers can monitor service statuses in real-time through the provided web page.